PERBANDINGAN SISTEM EKONOMI DAN CIRI UTAMA EKONOMI SYARIAH - Maryam Batubara; Assyfa Urrahman; Dea Rahma Novita; Hafizah Mahira Nasution; Rizky Aulia Lubis (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2023)
Each country has a different economic system. The system adopted by a country is usually in accordance with that country's ideology. For example, a system based on Islamic sharia, namely the Islamic economic system. Those who adhere to this system are Islamic countries in the world, but several countries, especially Indonesia, have implemented an Islamic economic system with the presence of several banks labeled sharia. The economic system is a combination of two words consisting of "system" and "economy". The Islamic economic system, for example, prioritizes personal interests and public interests as long as it does not conflict with the rules of Islamic law. This system is also called the Islamic economic system. Islamic economics is a science that studies human economic behavior whose behavior is regulated based on the rules of the Islamic religion and based on monotheism which is summarized in the pillars of faith and the pillars of Islam. The Islamic economic system is economic science applied in daily practice for individuals, families, community groups, and governments/authorities in order to regulate the factors of production, distribution, and utilization of goods and services produced subject to regulations/legislation. Islam.